Investment in Education: A Panacea for National Economic Vibrancy - Akpan, Ezekiel O.; Ozuruoke, Allen Anthony (Mediterranean Journal of Social Sciences, 2012)
This paper introduces the issue at stake here by highlighting on the meaning of investment in Educationusing dictionary definition. It expresses the bodies that ought to be involved and be responsible in investingand financing Education in Nigeria to give it the right boost. The paper further talk about the fundingadministration and planning of investment in education sectors presented in a table and how this willculminate to economic vibrancy when all the areas that need to be taken care of through such investmentsare considered appropriately and recommended fore herein. This work is concluded by reiterating that theright fund should be invested through the right process on the right programme level area such as forequipment, facilities, and personnel as to achieve the desired national economic vibrancy.